Prolonged storage of purified granulocyte concentrates: Introduction of a new purification method. Issue 1 (16th November 2021) - Klinkmann, Gerd; Doss, Fanny; Goudeva, Lilia; Doss, Sandra; Blasczyk, Rainer; Milej, Magdalena; Koch, Stephanie; Mitzner, Steffen; Altrichter, Jens
Abstract: Background: Use of donor granulocyte concentrate (GC) has been limited due to its short storage time of 6–24 h, which is partially due to residual red blood cells (RBCs) and platelets and the resulting lactate production leading to an acidotic milieu. To increase this storage time, we developed a closed system procedure compatible with standard blood bank technologies to remove RBC and platelets and to enrich the GC. Methods: Standard GCs (sGCs) were sedimented, washed twice with 0.9% sodium chloride (NaCl), and resuspended in blood group‐identical fresh frozen plasma. The resulting purified GCs (pGCs) were then stored in platelet bags at a cell concentration of about 5 × 10 7  ± 1.8 × 10 7 leukocytes/ml without agitation at room temperature for up to 72 h. Cell count and viability, pH, blood gases, phagocytosis, and oxidative burst were monitored daily. Results: A significant reduction in RBC (98%) through sedimentation, and platelets (96%) by washing, purified the white blood cell (WBC) population and enriched the granulocytes to 96% of the WBC in the pGC. After 72 h of storage, over 90% of the initial WBC count of pGC remained, was viable (≥97%), and the granulocytes exhibited a high phagocytosis and oxidative burst functionality, comparable to sGC after 24 h. Conclusion: Purification extends the maximum storage period of GC from 24 to 72 h and may therefore improve the availability of GC and its clinical use.